2022
DOI: 10.5334/pb.1086
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Ties with Secret Agendas During the Pandemic: Conspiracy Mentality is Associated with Reduced Trust in Political, Medical, and Scientific Institutions – but Not in Medical Personnel

Abstract: In a preregistered research, we examined the relationships between conspiracy mentality (i.e., the individual susceptibility to endorse conspiracy theories, Bruder et al., 2013) and trust in three actors of the COVID-19 crisis: 1) Political institutions, 2) scientific and medical institutions, and 3) the medical personnel. While the two former groups have played a direct or indirect role in decisions related to public health measures, the latter has not. We expected all these relationships to be negative and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…This confirmed H1, H2 and H3 of the present study. These results also confirm previous research findings by ( Erisen et al, 2021 ; Hameleers, 2021 ; Nera et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This confirmed H1, H2 and H3 of the present study. These results also confirm previous research findings by ( Erisen et al, 2021 ; Hameleers, 2021 ; Nera et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although some previous studies examined conspiracy mentality as a predictor (e.g. Mikušková, 2021 ; Nera et al, 2022 ), we decided to approach it as a dependent variable following the prevalent line of research (e.g. Bertin et al, 2020 ; Landrum & Olshansky, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, conspiracy beliefs regarding HIV/AIDS was found to be a barrier to preventive efforts of the disease in relation to medical mistrust [ 63 ]. Recently, a study that was conducted in Belgium and France showed a harmful effect of conspiracy mentality reflected in less trust in medical and scientific institutions [ 64 ]. Furthermore, genocidal HIV beliefs was linked to less public support and participation in HIV-related programs as shown by Laura Bogart et al in South Africa [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that trust in health authorities is a critical factor in vaccine acceptance (MacDonald, 2015), especially during pandemic times (Badur et al., 2020; Jennings et al., 2021; Nera et al., 2022; Turhan et al., 2022). An analysis using data from 149 countries shows that trusting healthcare workers over your close ones for medical advice is associated with increased vaccination uptake (de Figu, 2020).…”
Section: Introductionmentioning
confidence: 99%